Reconfiguring photonic metamaterials with currents and magnetic fields - Valente, João (2015)
We demonstrate that spatial arrangement and optical properties of metamaterial nanostructures can be controlled dynamically using currents and magnetic fields. Mechanical deformation of metamaterial arrays is driven by both resistive heating of bimorph nanostructures and the Lorentz force that acts on charges moving in a magnetic field. With electrically controlled transmission changes of up to 50% at sub-mW power levels, our approaches offer high contrast solutions for dynamic control of metamaterial functionalities in optoelectronic devices.